Hindu nationalism : a reader - Jaffrelot, Christophe Editor: Jaffrelot, Christophe (Orient black swan, 2017)
"Hindu nationalism came to world attention in 1998, when the Hindu nationalist Bharatiya Janata Party (BJP) won national elections in India. Although the BJP was defeated nationally in 2004, it continues to govern large Indian states, and the movement it represents remains a major force in the world's largest democracy. This book presents the thought of the founding fathers and key intellectual leaders of Hindu